Violence Against Women in Turkey and the Impact of Civil Society - Ziabara, Eleni; Mikroudaki, Konstantina; Papazafeiropoulou, Christina (HAPSc Policy Briefs Series, 2021)
In recent years, gender equality and women’s rights have been in the spotlight of international policymaking. However, in many cases, those efforts are not met with equal results. Women internationally continue to face discriminatory behavior and violence in all forms, both in socio-economic and political life. In Turkey, this issue remains largely unsanctioned, encouraging this type of violation of women’s basic human rights. Civil society organizations in Turkey play a very important part in applying pressure on the government and raising awareness on the importance of protecting women’s rights and eradicating gender-based violence. This policy brief examines the current situation of women rights in Turkey as well as the impact of civil society in the protection and empowerment of women.